Analytic thinking predicts accuracy ratings and willingness to share COVID-19 misinformation in Australia - Nurse, Matthew S.; Ross, Robert M.; Isler, Ozan; Van Rooy, Dirk (Memory & cognition, 2022)
The classical account of reasoning posits that analytic thinking weakens belief in COVID-19 misinformation. We tested this account in a demographically representative sample of 742 Australians. Participants completed a performance-based measure of analytic thinking (the Cognitive Reflection Test) and were randomized to groups in which they either rated the perceived accuracy of claims about COVID-19 or indicated whether they would be willing to share these claims. Half of these claims were previously debunked misinformation, and half were statements endorsed by public health agencies. We found that participants with higher analytic thinking levels were less likely to rate COVID-19 misinformation as accurate and were less likely to be willing to share COVID-19 misinformation. These results support the classical account of reasoning for the topic of COVID-19 misinformation and extend it to the Australian context.